Examining Fraud Hexagon on Fraudulent Financial Reporting in LQ45 Companies Listed on Indonesia Stock Exchange 2021–2024 - Kesi Ramadani; Sri Rahayu; Netty Herawaty (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to empirically prove the effect of fraud hexagon on fraudulent financial statements. The independent variables used in this study are stimulus, rationalization, opportunity, capability, arrogance, and collusion. Meanwhile, the dependent variable in this study is fraudulent financial statements. Research Methods: This study is a quantitative study. The population in this study consists of LQ45 companies listed on the Indonesia Stock Exchange for the period 2021-2024. The sample in this study was taken using purposive sampling with a sample size of 26 companies. The total observations were 104 observations, and after data processing, 1 outlier was found, so the total final observations were 103. The data analysis used in this study used secondary data sourced from the official website of the Indonesia Stock Exchange. The analysis technique used was multiple linear regression analysis with the assistance of SPSS software version 31.Finding/Results: The results of this study indicate that capability and collusion influence fraudulent financial reporting. Meanwhile, stimulus, rationalization, opportunity, and arrogance do not influence fraudulent financial reporting.